Review of radiation oncology emergencies in Lagos University Teaching Hospital, Nigeria - Adegboyega, Bolanle; Sowunmi, Anthonia; Alabi, Adewumi; Ojifinni, Oludoyinmola Omobolade; Adenipekun, A (South African journal of oncology, 2019)
Background: Radiation oncology emergencies (ROEs) are common in metastatic or locally advanced cancer accounting for a large proportion of radiotherapy indications in poor resource settings. Aim: To review pattern, presentation and outcome of ROEs in Lagos University Teaching Hospital (LUTH) and compare with an earlier study in the northern part of the country for possible geographical variation. Setting: A retrospective review of ROE record from 2008 to 2016 in LUTH. Method: Demographic data, clinical presentation, treatment and outcomes were analysed using charts and frequency tables. Results: Total of 458 cases of oncologic emergencies were reviewed. The mean age was 52.3 years with a male-to-female ratio of 1:2.2. The majority (85%) of the patients presented in stage IV, 10% stage III and 5% stage II diseases. Spinal cord compression was the commonest presentation seen in 53.9% of cases, brain metastases in 22.1% of patients and tumour haemorrhage in 22.5% of patients. Time from the onset of symptoms to treatment was between 24 and 48 h in 16.4%, > 48 h to 1 week in 64.4% and above 1 week in 19.2%. There was a complete or significant response in signs and symptoms in 77%, no improvement in 11% and 1.1% had disease progression. Conclusion: This study showed a varied pattern of presentation in ROEs from what was obtained in northern Nigeria, with spinal cord compression being the commonest in south west Nigeria. Despite a delayed onset in treatment, radiation therapy is vital in oncology emergencies management. There is a need for accessible functional radiotherapy centres in Nigeria to combat the delays in commencing treatment.
openalex: W2961553842 mag: 2961553842
Keywords: openalex:import

Social barriers to diagnosis and treatment of breast cancer in patients presenting at a teaching hospital in Ibadan, Nigeria - Pruitt, Liese C.C.; Mumuni, Tolulope; Raikhel, Eugene; Ademola, Adeyinka; Ogundiran, Temidayo O.; Adenipekun, A; Morhason-Bello, Imran O.; Ojengbede, Oladosu; Olopade, Olufunmilayo I. (Global Public Health, 2014)
AbstractGlobally, breast cancer is the most frequent malignancy in women, and stage at diagnosis is a key determinant of outcome. In low- to middle-income countries, including Nigeria, advanced stage diagnosis and delayed treatment represent a significant problem. That social barriers contribute to delay has been noted in previous research; however, few specific factors have been studied. Using semi-structured interviews, this study identifies social barriers to diagnosis and treatment for patients who presented at University College Hospital Ibadan, Nigeria. Transcripts from the interviews were coded and analysed thematically. Thirty-one patients and five physicians were interviewed. The median age of patients was 51 (range: 28 to above 80), 83% were Christian and 17% were Muslim. Preliminary analysis showed that delays in diagnosis reflected a lack of education as well as the utilisation of non-physician medical services such as pharmacists. Delays in treatment were often due to fear of unanticipated surgery and cost. The majority of women did not know the cause of their breast cancer, but some believed it was caused by a spiritual affliction. This study suggests that further education and awareness of breast cancer for both patients and providers is needed in order to increase early stage diagnosis.Keywords: breast cancerNigeriaqualitative researchsocial barriers to healthcarenon-communicable diseases
openalex: W2085201092 mag: 2085201092
Keywords: openalex:import